Computational complexity of the graph approximation problem - Ageev, A. A.; Il’ev, V. P.; Kononov, A. V.; Talevnin, A. S. (Journal of applied and industrial mathematics, 2007)
The computational complexity of the graph approximation problem is investigated. It is shown that the different variants of this problem are NP-hard both for undirected and directed graphs. A polynomial-time approximation scheme (PTAS) for one of the variants is presented.[PUBLICATION ABSTRACT]